Hepatic capsular rupture in pregnancy. (December 2016) - Frise, Charlotte J; Davis, Peyton; Barker, Graham; Wilkinson, Douglas; Mackillop, Lucy
The syndrome of haemolysis, elevated liver enzymes and low platelets is a rare condition specific to pregnancy, affecting approximately 5–20% of all pre-eclamptic pregnancies. Described here is a woman in her first pregnancy, who experienced an intrauterine death following a significant hepatic haematoma and capsular rupture, in the absence of classical clinical features suggestive of pre-eclampsia. The events that followed suggested haemolysis, elevated liver enzymes and low platelets syndrome as the likely diagnosis. The patient's clinical course highlights the difficulties that may be encountered when making decisions about pregnant women with complicated medical and obstetric issues.